The Effect of Discharge Planning on Ability of Parents to Care for Children After Diarrhea At Labuang Baji General Hospital - Awaliah, Nur Rahmah; Aryadi, Anggi; Randika, Rendi; Rasyid, Djusmadi; Ariyanti, Sri; Wahyuni, Tri; Islaeli, Islaeli (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Systematic nursing services need to focus on identifying and solving problems, and it is hoped that nurses play a role in helping families in providing care at home through the necessary health education for clients. This activity will run more effectively with early planning and health education, with the hope that client care can continue. So discharge planning is very necessary. This study aims to determine the effect of discharge planning on parents' ability to care for children after diarrhea at RSUD Labuang Baji Makassar. This research is a quantitative research with a Quasi Experimental design. The population studied were parents with children suffering from diarrhea who were treated at Labuang Baji Hospital, Makassar. With a sample size of 60 respondents. The sampling technique is purposive sampling. The sample was divided into two groups, namely the control group and the treatment group. After both groups were observed regarding knowledge, attitudes and skills. The treatment group was given the dischaege planning intervention, while the control group was not given the intervention. Data were collected using observation sheets and questionnaires with assessments according to the Gutman and Likert scales. Data analysis used t-test, Chi-Square, and Odds Ratio, with a significance level of α = 5% (0.05). Analysis of results in the treatment group using t-test. It was found that there was a significant influence between discharge planning on parents' ability to care for their children after diarrhea. with the expected value (p = 0.00) smaller than the value (0.005). and in the Chi-Square (Fisher's Exact Test) the value P = 0.00 < 0.05 is obtained which can be concluded that there is a relationship between discharge planning and the ability of parents to care for children after diarrhea, whereas in the analysis using the Odds Ratio of the value is 7.5, meaning . Parents who were given discharge planning intervention were 7 times more likely to have greater knowledge, skills and attitudes compared to parents who were not given discharge planning intervention. Meanwhile, in the control group, no influence or relationship was found with the expected t-test value p=0.32 > 0.05 and Chi-Square p=1,000 > 0.05. The conclusion is that there is an influence of discharge planning on parents' ability to care for children after diarrhea.